Genetic and chromosomal alterations in Kenyan Wilms Tumor. Issue 11 (14th August 2015) - Lovvorn, Harold N.; Pierce, Janene; Libes, Jaime; Li, Bingshan; Wei, Qiang; Correa, Hernan; Gouffon, Julia; Clark, Peter E.; Axt, Jason R.; Hansen, Erik; Newton, Mark; O'Neill, James A.; et al.
<x xml:space="preserve">Abstract</x> Wilms tumor (WT) is the most common childhood kidney cancer worldwide and poses a cancer health disparity to black children of sub‐Saharan African ancestry. Although overall survival from WT at 5 years exceeds 90% in developed countries, this pediatric cancer is alarmingly lethal in sub‐Saharan Africa and specifically in Kenya (36% survival at 2 years). Although multiple barriers to adequate WT therapy contribute to this dismal outcome, we hypothesized that a uniquely aggressive and treatment‐resistant biology compromises survival further. To explore the biologic composition of Kenyan WT (KWT), we completed a next generation sequencing analysis targeting 10 WT‐associated genes and evaluated whole‐genome copy number variation. The study cohort was comprised of 44 KWT patients and their specimens. Fourteen children are confirmed dead at 2 years and 11 remain lost to follow‐up despite multiple tracing attempts. TP53 was mutated most commonly in 11 KWT specimens (25%), CTNNB1 in 10 (23%), MYCN in 8 (18%), AMER1 in 5 (11%), WT1 and TOP2A in 4 (9%), and IGF2 in 3 (7%). Loss of heterozygosity (LOH) at 17p, which covers TP53, was detected in 18% of specimens examined. Copy number gain at 1q, a poor prognostic indicator of WT biology in developed countries, was detected in 32% of KWT analyzed, and 89% of these children are deceased. Similarly, LOH at 11q was detected in 32% of KWT, and 80% of these patients are deceased. From this genomic analysis, KWT biology appears uniquely aggressive and treatment‐resistant. © 2015 The Authors. Genes, Chromosomes & Cancer Published by Wiley Periodicals, Inc.